Development of Mathematics Learning Tools by Implementing Numbered Head Together Type Cooperative Models to Improve Students' Mathematical Understanding Ability in Matrix Topic - Evi Zahara, Evi Zahara; Murni, Atma; Hutapea, Nahor Murani (FKIP-Universitas Riau, 2020)
Students' mathematical understanding ability in Matrix material of Senior High Schools is still low. This is due to students being less active in learning, teaching materials are still limited and in learning teachers are more accustomed to presenting formulas instantly. This study aims to produce a valid, practical, and effective learning tool by implementing a cooperative model of Numbered Head Together (NHT) to improve students' mathematical understanding abilities in the Matrix Class XI material. The development model used was the Borg and Gall model. Data collection instruments used in this study were interview guides, questionnaires, and tests. The average validation results for RPP is 3.81 and for LKPD is 3.84 with a very valid category. Limited testing of 15 students obtained 91.22% percentage of student responses categorized as very practical. Field trials on 25 students obtained a percentage of the response of students 90.20% categorized as very practical. The results of the effectiveness test indicate that the students' mathematical understanding ability is increasing.